EVALUASI PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) PADA MASA PANDEMI COVID-19 DI PUSKESMAS TEMANGGUNG - Laila Fadillah Maulidati; Chatila Maharani (Jurnal Kesehatan Masyarakat (Undip), 2022)
The most common comorbidities among Covid-19 patients are hypertension and diabetes mellitus. To prevent chonic diseases such as hypertension and diabetes mellitus, the government through BPJS Kesehatan manage a chronic disease management programs (Program pengelolaan penyakit krnonis-Prolanis). The pandemic has impacted all aspects including Prolanis activities. This study aims to find out the differences between input, process, and output of the Prolanis before and during the Covid-19 pandemic at the Temanggung public health center. The research used qualitative research. The informants in this study consisted of Prolanis management officers, Prolanis participants who suffered from hypertension, and type 2 diabetes mellitus. Data was collected through in-depth interviews, observations, and secondary data. The results of this study explained there were differences on input categories (money and material), all process categories (planning, organizing, actuating, controlling), and output of the indicators for visiting participants. Meanwhile, for the input categories of man, machine, and method as well as the output of the the controlled Prolanis participant ratio (Rasio Peserta Prolanis Terkendali-RPPT) indicator there was no difference compared to before and during the pandemic. This research recommended for health workers to increase their role as educators to promote the importance of joining Prolanis, so the participants are motivated to make regular visits both during and after the pandemic.